Synchronous computer-mediated communication as a peer observation tool. (16th August 2021) - Bates, Paul; Donaghue, Helen
Abstract: Peer observation plays a key developmental role in initial teacher education courses. However, potential benefits can be limited due to time constraints and the rigidity of individual observation tasks. This article examines the use of synchronous computer-mediated communication (SCMC) as a peer observation tool on a CELTA course. We analyse SCMC feeds and participant interviews to discover how CELTA trainees and tutors use SCMC during observations and how participants perceive SCMC as an observation tool. SCMC enabled trainees to identify and solve problems, share ideas and opinions, give constructive feedback, and reflect on their own and their peers' teaching. Tutor questions were an important resource in prompting these actions. SCMC seemed to help build rapport and democratize feedback as trainees initiated discussions, chose topics, and interacted with each other and the tutor. Participants found SCMC engaging and useful. Results suggest that SCMC enhanced collaboration, dialogue, and reflection during peer observation.